DESA WONOJATI MENUJU MANDIRI LESTARI: LITERASI LESTARI,PENGOLAHAN SAMPAH,BUDIDAYA MAGGOT,ECOENZYM,DAN DIGITALISASI UMKM - Khilyatun Nisa , Nugraheni; Mochammad , Alfiansyah; Rizky Angga , Pratama; Zahra Fadia Siti , Halizah; Rega Ayu , Darasuta; Tirsa , Febiyanti; Mani'ah Mellow , Kusmiyana; Echa Putra , Prakassyah; Muhammad Daffa Alvin , Ekananda; Iftia Yasmin , Ghinnanafsi; Al Rafi Afzaal Fazl , Rab; Niken Aulia , Septiana; Chika Adinda Difia , Lestari; Erik , Kusuma (PAPUMA: Journal of Community Services, 2025)
In the issues present in the village of Wonojati, Gondangwetan District, Pasuruan, they are still related to suboptimal waste management and the low ecological awareness of the community. This situation encourages students from the Community Service Program of Jember University to implement an integrated community service program with the theme "Wonojati Village Towards Sustainable Independence." The methods used include surveys and village coordination, environmental literacy based on children's understanding to instill environmental awareness from an early age, the establishment of a village waste bank as a sorting center, training on Black Soldier Fly (BSF) maggot cultivation to process organic waste while also supplementing feed for catfish, as well as training in making ecoenzymes. The produced maggots can replace up to 50% of pellet feed in catfish farming, thus reducing production costs. Processed products in the form of catfish flakes and catfish roll cakes are then strengthened through branding and digitalization of MSMEs with the creation of logos and geotagging business locations. The results show an increase in ecological awareness, a reduction in waste volume, cost efficiency in animal feed, and an improvement in the competitiveness of MSME products. In conclusion, the integration of literacy, waste management, and the digitalization of MSMEs can strengthen the economic and ecological independence of communities towards sustainable villages